Acid soils amelioration – modern opinions and ways forward - Tsapko, Yu.L.; Desyatnik, K.A.; Ogorodnyа, A.I. (AgroChemistry and Soil Science, 2018)
The article is devoted to reviewing the results of long-term scientific research on topics related to the justification of the use of calcium-containing meliorants and phytomelioration measures to improve the quality of acid soils. The advantages of the local way of introducing calcium-containing meliorants on acid soils are highlighted. It is emphasized that in order to save material and energy resources, it is expedient to use local raw materials and calcium-containing waste products as meliorants, which considerably reduces the costs of their transportation and procurement, and at the same time solves the problem of waste utilization. Differentiated action of lime meliorants of natural and industrial origin is established on the productive function depending on the soil on which they are applied. The role of phytomelioration as a biological method of soil improving, which is carried out through the use of phytopotentials of competently harvested crops, is rather mild and environmentally friendly compared to chemical amelioration